Antipyretic Activity of Ethanol Fraction of Pandan Laut Leaves (Pandanus odorifer) against Male Mice (Mus musculus) Induced by DPT-HB Vaccine - Nurhamidah Nurhamidah; Elvinawati Elvinawati; Dewi Handayani; Sura Menda Ginting; Nursela Wahyuni (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
Fever is a condition where the body temperature exceeds 37 °C caused by disease or inflammation resulting from a viral or bacterial infection. People consume synthetic drugs or commonly called antipyretics, to treat fever. This study aims to determine the antipyretic activity of the Ethanol fraction of sea Pandanus leaves (Pandanus odorifer) against male mice (mus musculus) induced by the DPT-HB vaccine. Sample extraction was done by the maceration method with various solvent polarities (non-polar; n-Hexane, semi-polar; Ethyl Acetate, polar; Ethanol). All three fractions were tested for their secondary metabolites of Flavonoids with antipyretic activity. In addition, an antipyretic activity test was carried out on male mice induced by the DPT-HB vaccine-induced by an intramuscular method in the lower abdomen. An infrared thermometer (ANENG AN201) measured the mice's body temperatures every 30 minutes for 180 minutes after induction. Phytochemical identification results show that the n-Hexane fraction contains Tannins and Steroids as secondary metabolites. The Ethyl Acetate fraction contains Tannins, Triterpenes, Steroids, and the Ethanol fraction contains Tannins, Triterpenes, Steroids, Saponins, and Flavonoids. The antipyretic activity test results show that the Ethanol fraction of sea Pandanus leaves (Pandanus odorifer) has the potential to be antipyretic against mice (Mus musculus), and the most effective antipyretic effect was found in infraction with a dose of 600 mg/kg body weight.